Answers

The Brainliest Answer!
2014-07-01T15:48:39+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
You need to multiply each term of one factor to every term of the others.

For example, (a+b) (c+d)

Multiply a to c = ac
multiply a to d = ad
multiply b to c = bc 
multiply b to d = bd

So,   (a+b) (c+d)   =   ac + ad + bc + bd

Note that you may combine constants and similar terms.

Similar terms are those with the same variables raised to the same power.
Example: x² + x² = 2x²
2 5 2